Impact of science on society - Russell, Bertrand (London, 2007)
Many of the revolutionary effects of science, in terms of technology and in our outlook, are obvious enough. Russell saw in the 1950s, as is all too clear today, that there are many negative aspects of scientific innovation. In The Impact of Science on Society, he argues that science offers the world greater well-being than it has ever known before on the condition that prosperity is dispersed, power is diffused, birth rates do not become too high and war is abolished. Russell sees that this is a tall order, but remains essentially optimistic. He imagines mankind in a 'race between human skill as to means and human folly as to ends', but believes human society will ultimately choose the path of Reason rather than the alternative of Death.
Keywords: Science and civilization